2015
DOI: 10.2196/mhealth.4222
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mobile Phone-Based Care for Weight Control in Metabolic Syndrome Patients: Randomized Controlled Trial

Abstract: BackgroundOverweight and obesity, due to a Westernized diet and lack of exercise, are serious global problems that negatively affect not only personal health, but national economies as well. To solve these problems, preventative-based approaches should be taken rather than medical treatments after the occurrence of disease. The improvement of individual life habits, through continuous care, is thus a paramount, long-term treatment goal. This study describes the effects of ubiquitous health care (uHealth care) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 47 publications
(39 reference statements)
0
98
0
Order By: Relevance
“…The use of digital technology in health care is gaining popularity as a potentially cost‐effective means of health promotion and disease prevention , and the Korean government promotes the approach as “Smartcare” . For example, wearable activity trackers motivate people to increase their physical activity by helping them track their own activity and receive feedback .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of digital technology in health care is gaining popularity as a potentially cost‐effective means of health promotion and disease prevention , and the Korean government promotes the approach as “Smartcare” . For example, wearable activity trackers motivate people to increase their physical activity by helping them track their own activity and receive feedback .…”
Section: Introductionmentioning
confidence: 99%
“…However, one third of people cease using the devices within 6 months of purchase, suggesting low levels of long‐term sustained engagement for some users . Ineffectiveness or low levels of effectiveness could be the reasons for this . Patel et al suggested that wearable devices are facilitators, rather than drivers, of behavior change .…”
Section: Introductionmentioning
confidence: 99%
“…This sector is still emerging. To make the health information platform stronger, a growing number of web portals, online health forums, and text messaging services are accommodating the exchange of health-related information [1][2][3]. Digital innovation is an idea, practice or object that is perceived as new domain by an individual or some other unit of adoption [4].…”
Section: Introductionmentioning
confidence: 99%
“…When considering how to provide such services at scale, e-health, and more recently mhealth [7] and u-health [8], technologies show promise in augmenting traditional services and can be adapted potenitally to all aspects of care [9]. A consistent theme is that such technologies can also address poor youth engagement with mental health services [10].…”
Section: Introductionmentioning
confidence: 99%